Analisis Implementasi Kebijakan Permenkes Nomor 67 Tahun 2016 Tentang Penanggulangan Tuberkulosis di Kabupaten Kudus Tahun 2021 (Studi Kasus di Wilayah Kerja Puskesmas Purwosari Kudus) - Nugraha, Eprileo; Wahyono, Bambang (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2023)
Tuberculosis is an infectious disease that is still a public health problem and one of the causes of death so it is necessary to carry out TB control programs on an ongoing basis. The purpose of the study was to analyze the implementation of policies on TB control in Kudus Regency. The number of positive cases found in Kudus Regency in 19 health centers in 2019 was 681 cases. The case notification rate = CNR of all tuberculosis cases per 100,000 population is 79 per 100,000 population. Based on data obtained by interviews with TB program management officers of the Kudus Regency health office, the highest number of cases were in the Kudus City District work area at the Purwosari Health Center as many as 67 cases with 41 men and 26 women, with a prevalence of 6.7 percent and an incidence rate of 31.3 percent. This research was conducted from August to September 2021. This type of research is descriptive qualitative research with informant retrieval techniques by purposive sampling. The main informants are TB program managers at health center and associate doctors at health center. Test validity with source triangulation informants to the head of the Purwosari Kudus health center, health survey officers and tuberculosis patients. The results showed that the implementation of policy implementation has not run optimally. Of several variables that affect the implementation of policy implementation, namely; human resources; cross-sector relations; and environmental conditions, in the study, it was found that there were still variables that had not run optimally so that they hampered the implementation of this implementation, namely the lack of community support in TB control, and affected by the COVID 19 pandemic.